PENGARUH PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA SURAKARTA - Anita Wijayanti, Eka Arif Rustanto Siti Nurlaela (PARADIGMA, 2014)
This research aims to determine the influence of partial and simultaneous hotel tax and restaurant tax on district own source revenue Surakarta. This type of research is quantitative research. Secondary data sources. The research instrument is a data collection technique that takes the data from the documentation. Population as well as the sample in this research is the realization of hotel tax, restaurant tax, and district own source revenue Surakarta years 2009-2012 were taken by using the method of census of the Department of Revenue, Finance and Asset Management Surakarta. Methods of data analysis using the classical assumption includes normality test, multicollinearity, heteroscedasticity test and autocorrelation test. Hypothesis testing using multiple linear regression t test, F test and the coefficient of determination. First hypothesis t count > t table (4.024> 2.014) and significance 0.000 < 0.05 then Ha is accepted, H1 is partially the result of hotel tax influence on district own source Surakarta. Second hypothesis, - table t â¤ t â¤ t table (-2.014 â¤ 0.568 â¤ 2.014) and a significance of 0.573 > 0.05 then Ha is rejected, H2 partially restaurant tax result does not influence on district own source revenue Surakarta. Third hypothesis, F count > F table (42,786 > 3,204) and significance < 0.05 (0.000 < 0.05), the Ha accepted that H3 outcome hotel tax and restaurant tax simultaneously influence on district own source revenue Surakarta.Keywords : District Own Source Revenue